Household fuel choice in urban Kenya: A multinomial logit analysis - David Waweru; Naftaly Mose (Financial Internet Quarterly, 2022)
This study applied a logistic regression model to determine the odds ratio of selecting clean ver- sus unclean energy as the main household fuel choice. This study also undertook to establish the coefficients of the factors determining household fuel energy choice. A large microeconomic dataset from KIPPRA's comprehensive study and analysis on fuel use patterns in Kenya (2010) was employed to carry out the analysis. This study employed a multinomial logit regression mod- el to determine the fuel choices and patterns of cooking fuels in urban Kenyan households. The results showed that in addition to income, there are several socio-demographic factors such as education, gender, and age that were important in determining household fuel choice. To en- courage clean fuel use, the authorities should carry out public education campaigns, and ensure the availability of these fuels in all areas to avoid harmful effects of biomass fuels and kerosene, and more modern and efficient appliances should be made available at affordable rates to en- sure more efficient use of these forms of clean energy.
Keywords: D15; C55; Q42; Q41; 330; fuel; choices; households; energy; cooking; urban; logit